2013
DOI: 10.1158/1535-7163.mct-12-1107
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Scaffold Proteins as Superagonists of TRAIL Receptor 2–Induced Apoptosis

Abstract: Activation of TNF-related apoptosis-inducing ligand receptor 2 (TRAILR2) can induce apoptosis in a variety of human cancer cell lines and xenografts, while lacking toxicity in normal cells. The natural ligand and agonistic antibodies show antitumor activity in preclinical models of cancer, and this had led to significant excitement in the clinical potential of these agents. Unfortunately, this optimism has been tempered by trial data that, thus far, are not showing clear signs of efficacy in cancer patients. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 43 publications
1
87
0
Order By: Relevance
“…These findings suggest that other therapies that synergize with TRAIL, such as quinacrine, are worth investigating for combinatorial activity with ONC201 (13). By a similar notion, these findings also suggest that sorafenib may sensitize other TRAIL-based agents such as TRAIL-receptor agonists that have been developed including antibody- and protein scaffold-based approaches (1416). …”
Section: Discussionmentioning
confidence: 72%
“…These findings suggest that other therapies that synergize with TRAIL, such as quinacrine, are worth investigating for combinatorial activity with ONC201 (13). By a similar notion, these findings also suggest that sorafenib may sensitize other TRAIL-based agents such as TRAIL-receptor agonists that have been developed including antibody- and protein scaffold-based approaches (1416). …”
Section: Discussionmentioning
confidence: 72%
“…28 Other recent studies have also demonstrated that multivalent presentation of peptide and protein ligands is sufficient to induce enhanced cellular bioactivity relative to an unconjugated monovalent control. [63][64][65] In a particularly noteworthy study, multivalent conjugates of ephrin-B2-HyA, synthesized using the conjugation protocol described here, demonstrated enhanced differentiation of neural progenitor cells in vitro and in vivo. 66 In addition, the authors reported that clustering of ephrin-B2 receptors on the cell surface and the downstream pathway activity were correlated directly with ephrin-B2 valency, thereby providing further evidence that the multivalent presentation of protein ligands was sufficient to enhance the activation of their cellular targets.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to full-length antibodies, different scaffolds such as atrimers (31) or multivalent monobodies (32,33) are under evaluation to target DRs. However, the lack of clinical efficacy observed with untargeted DR5 agonistic antibodies illustrates that the activity of these molecules in vitro may not necessarily translate into clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%